Functional and Cognitive Decline Is Associated With Increased Endothelial Cell Inflammation and Platelet Activation: Liquid Biopsy of Microvesicles in Community- Dwelling Octogenarians - Chiva-Blanch, Gemma; Vilella-Figuerola, Alba; Padró, Teresa; Formiga, Francesc; Ferrer, Assumpta; Badimon, Lina (Frontiers in Cell and Developmental Biology, 2021)
Increased life expectancy is usually associated with comorbidities, such as cardio and cerebrovascular disease causing impaired functionality. A common underlying cause of these comorbidities is vascular inflammation and injury. Elevated levels of circulating microvesicles (cMV), as a product of a hemostatic and inflammatory cell activation, could be direct mapping of an imbalanced hemostasis. In this manuscript, we aimed to investigate by liquid biopsy whether successful aging can be discriminated by cMV levels and phenotype. To this purpose, we included 135 community-dwelling octogenarians in a cross-sectional study. Successful aging was defined as good functional (Barthel Index >90 points, and Lawton index score >7/4 points for women and men, respectively) and cognitive status (Spanish version of the Mini-Mental State Examination -MEC- >24 points) and no need for institutionalization. Total, annexin V positive (AV+), and AV- cMV from different cell origins from the vascular compartment were phenotypically characterized and quantified from fasting plasma samples by flow cytometry. Successful aging was associated with lower plasma concentrations of total and AV+ CD141+/CD41+-CD61+, and PAC1+/AV+, CD141+/AV+, and CD36+/AV- cMV. From these phenotypes, ROC curve analyses revealed that CD141+/AV+ and CD141+/CD41+-CD61+/AV+ endothelial- and platelet-derived cMV properly discriminated successful and non-successful aging with an AUC (95%CI) of 0.655 (0.551, 0.758), P= 0.005, and 0.638 (0.535, 0.741), P= 0.013, respectively. In conclusion, successful aging is associated with low levels of cMV released by endothelial cells and platelets, indicating lower endothelial cell inflammation and platelet activation. Our results contribute to the understanding of the link between unsuccessful aging, cognitive decline and vascular cell inflammatory disturbances.